“I Am Not My Bodies:” Transgender Embodiment in Nina Arsenault’s The Silicone Diaries - White, Zaren Healey (Atlantis)

(untitled) (Mount Saint Vincent University, 2016)
This article examines transgender embodiment through analysis of Canadian transgender performance artist Nina Arsenault and her autobiographical play The Silicone Diaries (2012b). I discuss Arsenault’s life writing, plays, and self-portraiture to explore how her pursuit of an exaggerated ideal of beauty simultaneously subverts essentialist notions of what it means to be a woman.This paper was awarded the second prize in the Women’s and Gender Studies et Recherches Féministes (WGSRF) Graduate Essay Prize competition in 2014.